2008
DOI: 10.1098/rstb.2008.0111
|View full text |Cite
|
Sign up to set email alerts
|

Diversification in a fluctuating island setting: rapid radiation ofOhomopterusground beetles in the Japanese Islands

Abstract: The Japanese Islands have been largely isolated from the East Asian mainland since the Early Pleistocene, allowing the diversification of endemic lineages. Here, we explore speciation rates and historical biogeography of the ground beetles of the subgenus Ohomopterus (genus Carabus) based on nuclear and mitochondrial gene sequences. Ohomopterus diverged into 15 species during the Pleistocene. The speciation rate was 1.92 Ma -1 and was particularly fast (2.37 Ma) in a group with highly divergent genitalia. Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
77
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 55 publications
1
77
0
Order By: Relevance
“…Among these species groups, the iwawakianus-insulicola group (Sota and Vogler, 2003) exhibits the most marked diversification in genital morphology. The six species are estimated to have diverged 0.76 million years ago, representing the most rapid speciation in this subgenus (Sota and Nagata, 2008). Previous molecular phylogenetic studies revealed that phylogenetic reconstruction of this subgenus is extremely difficult owing to introgressive hybridization between species and/or incomplete lineage sorting of ancestral polymorphism Vogler, 2001, 2003;Sota and Sasabe, 2006;Sota and Nagata, 2008).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Among these species groups, the iwawakianus-insulicola group (Sota and Vogler, 2003) exhibits the most marked diversification in genital morphology. The six species are estimated to have diverged 0.76 million years ago, representing the most rapid speciation in this subgenus (Sota and Nagata, 2008). Previous molecular phylogenetic studies revealed that phylogenetic reconstruction of this subgenus is extremely difficult owing to introgressive hybridization between species and/or incomplete lineage sorting of ancestral polymorphism Vogler, 2001, 2003;Sota and Sasabe, 2006;Sota and Nagata, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Ohomopterus diverged from its sister subgenus Isiocarabus in East Asia 2.14 million years ago during the Pleistocene (Sota and Nagata, 2008). Molecular phylogenetic studies using nuclear DNA revealed that this subgenus diverged into several species groups during the early Pleistocene, followed by differentiation within the species groups leading to the extant species (Sota and Vogler, 2003;Sota and Nagata, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a hybrid zone between Carabus maiyasanus and C. iwawakianus , a physical incompatibility between the male and female genitalia is an agent of endogenous selection (Kubota 1988; Kubota and Sota 1998; Sota and Kubota 1998). These two species are closely related (Sota and Nagata 2008; Takahashi et al. 2014) and exhibit little mate discrimination between conspecifics and heterospecifics; accordingly, interspecific mating occurs frequently (Sota and Kubota 1998).…”
Section: Introductionmentioning
confidence: 99%
“…These deal with beetles in Japan (Sota & Nagata 2008), land snails in Belau (Rundell 2008) and the Ogasawara Islands (Davison & Chiba 2008), iguanas in Fiji (Keogh et al 2008), crickets in New Zealand, Australia and New Caledonia (Pratt et al 2008), weevils in the Galápagos (Sequeira et al 2008) and moths in the Galápagos (Schmitz et al 2008) and Hawaii (Rubinoff 2008).…”
mentioning
confidence: 99%